Improving Oxidative Stability and Sensory Properties of Ale Beer by Enrichment with Dried Red Raspberries (Rubus idaeus L.). (2nd October 2021) - Yin, Hua; Deng, Yuan; Zhao, Junfeng; Zhang, Lehong; Yu, Junhong; Deng, Yang
Abstract: Red raspberry has attracted great interest due to its inherent antioxidant, anticarcinogenic, and antihyperglycemic effects. To brew a beverage with high antioxidant capacity and desirable sensory characteristics (malty aroma, hop aroma, fruit flavor, freshness, fullness, sweetness, sourness, and bitterness), dried red raspberries ( Rubus idaeus L.) (30 g L −1 wort) were added to beer at different stages of the brewing process (beginning of boiling, before fermentation, before conditioning) and compared to a control without added dried fruits. The beer was fermented with Saccharomyces cerevisiae for 7 days at 18 °C followed by a secondary fermentation of 3 days at 20 °C. The main physicochemical attributes (original gravity, ethanol content, pH, color, colloidal haze, viscosity, bitterness, diacetyl, acetaldehyde, higher alcohols, and esters), sensory characteristics, and major bioactive compounds were determined. A decline in pH and an increase in color were observed in the raspberry beers. Adding dried fruits at the beginning of boiling imparted the highest oxidative stability and total phenolic and flavonoid content (696 mg GAE L −1 and 510 mg QE L −1, respectively). Sensory analysis revealed that the most preferred product according to appearance, flavor, and taste was the beer with dried fruits added at the beginning of boiling.